Decision and choice - "Messick, Samuel (ed.); Brayfield, Arthur H.(ed.)" (London, 1964)
This book contains most of sidney siegel's published journal articles on the general topics of decision making and choice behavior, together with six specially prepared papers by behavioral scientists extending and discussing some of his work.
Keywords: Psychology